Unique determination of a penetrable scatterer of rectangular type for inverse Maxwell equations by a single incoming wave. (4th February 2019) - Hu, Guanghui; Li, Long; Zou, Jun
Abstract: This work is concerned with an inverse electromagnetic scattering problem in two dimensions. We prove that in the TE polarization case, the knowledge of the electric far-field pattern incited by a single incoming wave is sufficient to uniquely determine the shape of a penetrable scatterer of rectangular type. As a by-product, the uniqueness is also confirmed to inverse transmission problems modelled by scalar Helmholtz equations with discontinuous normal derivatives at the scattering interface.